Interallelic complementation at the pyrF locus and the homodimeric nature of orotate phosphoribosyltransferase (OPRTase) in Mucor circinelloides. - Velayos, A; Alvarez, M; Eslava, A; Iturriaga, E (1998)
Using 5-fluoroorotic acid (5-FOA) as a positive selection system we isolated mutants of Mucor circinelloides altered in the pyrimidine biosynthetic pathway. These mutants were found to be deficient either in orotidine-5'-monophosphate decarboxylase (OMPdecase), or in orotate phosphoribosyltransferase (OPRTase) activity. Complementation tests among mutants lacking OPRTase activity classified them into three groups, thus suggesting the possibility of interallelic complementation. To investigate this hypothesis a cDNA clone corresponding to the OPRTase-encoding gene of M. circinelloides was isolated by direct complementation of E. coli. The genomic copy transformed to prototrophy one member of each of the three classes of OPRTase-deficient mutants. We therefore concluded that they were all altered at the same locus, the pyrF locus. The corresponding alleles were cloned and sequenced. Comparisons of the amino acid sequence of M. circinelloides OPRTase with those of E. coli and S. typhimurium revealed a high degree of similarity in secondary and tertiary structure. As the two bacterial enzymes exist as dimers, a homodimeric quaternary structure of the M. circinelloides mature protein can be assumed. This would also explain the interallelic complementation between some pyrF mutants. The mutations found could affect either the active site or the structure of the dimer interface of the OPRTase.